KONTRIBUSI GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENGEMBANGKAN SELF CONTROL SISWA DI SMA DUA MEI CIPUTAT - Laila Nur Habibah; Siti Saniah; Irmawati Irmawati (Almarhalah | Jurnal Pendidikan Islam, 2021)
ABSTRACTThis study aims to describe the contribution of Islamic Religious Education teachers in developing self-control in students at SMA Dua Mei Ciputat. This type of research is a type of qualitative or non-statistical research. Qualitative research is an intensive search using scientific procedures to produce narrative conclusions both written and oral based on analysis of certain data. Sources of data in research are the subjects from which data can be obtained. The research subject was the Islamic Religious Education (PAI) teacher at SMA Dua Mei. According to Averill in M. Ghufron, self control is called personal control, namely behavior control, cognitive control and decision control. The conclusion of this study is that the teachers of Islamic Religious Education (PAI) at SMA Dua Mei Ciputat are sufficient to contribute in developing self-control for students at SMA Dua Mei Ciputat. It can be seen that the PAI teacher has tried to develop every aspect of self-control, namely the cognitive control aspect by providing more information about knowledge about Islam by integrating PAI learning material with the surrounding conditions, then the control aspect. The behavior (behavior control) of Islamic Education teachers provides habituation both to students inside and outside the classroom, such as discipline, accustoming students to praying in congregation, as well as aspects of decision control, where students are given the opportunity to have an opinion during discussions conducted with the guidance of the PAI teacher. PAI teachers also provide guidance and direction to students who violate school regulations. From the various contributions of Islamic Religious Education (PAI) teachers, it is certainly very influential on the development of student self-control, this can be seen from the habituation applied by Islamic Religious Education (PAI) teachers can provide positive changes to students, such as students having awareness in worshiping and participating in religious activities without coercion from the PAI teacher, students have self-confidence, and make students more interested in deepening the knowledge of Islam.Keywords: Teacher   Contribution,   Islamic   Education   and   Self-Control